Evaluation of the biological control agent Rotstop in controlling the infection of spruce and pine stumps by Heterobasidion in Latvia - Kenigsvalde, Kristine; Brauners, Indulis; Korhonen, Kari; Zaluma, Astra; Mihailova, Alina; Gaitnieks, Talis (Taylor & Francis AS, 2016)
The biological control agent Rotstop((R)) composed of a suspension of spores of Phlebiopsis gigantea (Fr.) Jul. is widely used for protecting conifer stumps from aerial infection by Heterobasidion species. The efficacy of Rotstop application on Norway spruce (Picea abies) and Scots pine (Pinus sylvestris) stumps was determined in several locations and at different seasons in Latvia. Mean efficacy in controlling natural infection by Heterobasidion spp. in spruce stumps was 64%, calculated on the basis of number of infected stumps, and 89%, calculated on the basis of area of infected wood on sample discs cut from the stumps. Corresponding proportions for pine were 82% and 95%. The results show that Rotstop can be successfully used for stump treatment in Latvia, although improved efficacy is desirable, particularly in spruce. A Latvian isolate of P. gigantea, selected from numerous isolates in preliminary tests, was included in one experiment and was shown to be as effective as the Rotstop isolate. In untreated spruce stumps Heterobasidion spp. and P. gigantea were present in the same stump three times more frequently than in untreated pine stumps. Heterobasidion spp. infection in untreated spruce stumps was low when P. gigantea covered more than 10% of stump dissection.
Keywords: Pinus sylvestris; Picea abies; rotstop; heterobasidion; stump treatment; Phlebiopsis gigantea; Picea abies stands; Norway spruce; intersterility groups; spore infections; Fomes annosus; wood moisture; root-rot; spp.; Southern Sweden